Keyword Recorder for Robot Framework - Amelia Kezia Gunawan (International Journal of Industrial Research and Applied Engineering, 2020)
In this era where Agile's popularity is growing fast in the IT industry, test automation becomes more and more crucial for Agile. However, test automation is time-consuming. For this reason, the student creates a tool named Keyword Recorder to create and generate test scripts — the most time-consuming part of test automation — intending to find a solution to speed up the test automation process. Keyword Recorder is a standalone program for web testing and is made to generate scripts for Robot Framework. It consists of two components: a browser, and a recorder. The browser is where the user do the web testing and the recorder’s job is to capture all the user actions along with the web elements during web testing and generate a Robot Framework’s test script based on the recorded actions.